2006
DOI: 10.1097/00000542-200611000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Laryngeal Nerve Palsy after Anterior Cervical Spine Surgery

Abstract: Endotracheal tube cuff deflation/reinflation and pressure adjustment do not reduce the incidence of vocal fold immobility in anterior cervical spine surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(10 citation statements)
references
References 12 publications
1
6
0
1
Order By: Relevance
“…[9] These complications occur as a result of direct surgical trauma, nerve division, pressure or stretch induced neuropraxia, and ETT-related vocal fold palsy. [310] Audu and colleagues[11] reported 3.2% incidence of vocal cord palsy after ACDF which is comparable to the results of our study (2.7%).…”
Section: Discussionsupporting
confidence: 90%
“…[9] These complications occur as a result of direct surgical trauma, nerve division, pressure or stretch induced neuropraxia, and ETT-related vocal fold palsy. [310] Audu and colleagues[11] reported 3.2% incidence of vocal cord palsy after ACDF which is comparable to the results of our study (2.7%).…”
Section: Discussionsupporting
confidence: 90%
“…With regards to anterior cervical spine surgery, lowering the ETT cuff pressure after placement of the retractor may influence postoperative dysphagia, sore throat, and hoarseness. However, a randomized controlled trial showed that pressure adjustment did not reduce the incidence of vocal cord immobility [11]. A small study from 2002 analysed patients undergoing anterior cervical spine surgery and data suggested a lower incidence of sore throat in patients with lower cuff pressures, while a recently performed observational study showed less recurrent laryngeal nerve palsy in patients with reduction of ETT cuff pressure [5,12].…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] The most likely mechanisms of RLN injury include indirect stretch or focal pressure on the nerve, 2 and the former was accepted by more researchers. 17,18 Based on this theory, ACCF is a more probable cause of hoarseness as ACCF needs more space and the retractor stretches more compared with ACDF. As a result, arytenoid dislocation is tend to be misdiagnosed when hoarseness occures after ACCF.…”
Section: Discussionmentioning
confidence: 99%